2015
DOI: 10.1021/acs.cgd.5b00304
|View full text |Cite
|
Sign up to set email alerts
|

Shape Control of Zn(II) Metal–Organic Frameworks by Modulation Synthesis and Their Morphology-Dependent Catalytic Performance

Abstract: Micro-and nanorods and plates of three porous Zn(II)-based metal−organic frameworks, [Zn 2 (oba) 2 (4-bpdb)] n •2(DMF) (TMU-4), [Zn(oba)(4-bpdh) 0.5 ] n •1.5(DMF) (TMU-5), and [Zn(oba)(4-bpmb) 0.5 ] n 1.5(DMF) (TMU-6) were synthesized by the coordination modulation method. The effects of concentration of modulator, temperature, and time of reaction on size and morphology have been investigated. Also, catalytic performance of TMU-5 nanosized metal−organic framework in Knoevenagel condensation reaction was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 35 publications
0
41
0
1
Order By: Relevance
“…Recent studies have shown that these gas adsorption capabilities can be further enhanced through the introduction of modulators during MOF synthesis, by altering the overall crystal growth process [14]. In anisotropic MOFs, such as those in the M2(dicarboxylate)2(N-ligand) series, the modulator-based growth control is dramatic and can significantly alter crystal aspect ratios [15][16][17]. The introduction of modulators during synthesis can target either the carboxylate (h00, 0k0) or the amino (00l) planes, inhibiting crystal growth along these planes and directing MOF crystal growth along unmodulated axes ( Figure 1) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that these gas adsorption capabilities can be further enhanced through the introduction of modulators during MOF synthesis, by altering the overall crystal growth process [14]. In anisotropic MOFs, such as those in the M2(dicarboxylate)2(N-ligand) series, the modulator-based growth control is dramatic and can significantly alter crystal aspect ratios [15][16][17]. The introduction of modulators during synthesis can target either the carboxylate (h00, 0k0) or the amino (00l) planes, inhibiting crystal growth along these planes and directing MOF crystal growth along unmodulated axes ( Figure 1) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In anisotropic MOFs, such as those in the M2(dicarboxylate)2(N-ligand) series, the modulator-based growth control is dramatic and can significantly alter crystal aspect ratios [15][16][17]. The introduction of modulators during synthesis can target either the carboxylate (h00, 0k0) or the amino (00l) planes, inhibiting crystal growth along these planes and directing MOF crystal growth along unmodulated axes ( Figure 1) [15][16][17]. Previous work has demonstrated the [Cu2(NDC)2(DABCO)]n (NDC = 1,4-naphthalene dicarboxylate; DABCO = 1,4-diazabicyclo[2.2.2]octane) member of the [M2(dicarboxylate)2(N-ligand)]n MOF series can be modulated to obtain rod or plate morphologies with the use of acetic acid (carboxylate) or pyridine (amino) modulators [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal methods are simple and effective techniques which include thermal decomposition and calcination [37][38][39][40][41][42][43]. Thermal decomposition, or thermolysis, is a chemical decomposition caused by heat [44][45][46][47][48][49][50][51].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…125 Da mesma forma, é também importante conhecer métodos de controle sobre a morfologia de nano-e microcristais de MOFs. 126 A Figura 7 mostra uma imagem de microscopia eletrônica de transmissão de alta resolução de um nanocristal monodisperso do material Zn-MOF-74, 127 onde os clusters metálicos e os canais hexagonais de diâmetro ~11 Å podem ser observados. De acordo com os autores, essa foi a primeira vez que dados de microscopia eletrônica permitiram a observação de um cluster metálico ligando a fase orgânica em uma MOF.…”
Section: Controlando O Tamanho E a Forma Das Partículasunclassified